Nature of particular structure position of the Antarctica - Pavlenkova, N. I. (Ukrainian Antarctic Journal, 2009)
Two specific structural features are typical for the Antarctica continent. These are its position in the South Pole area with strong symmetry relatively the Arctic Ocean, and a system of the oceanic ridges forming a ring around Antarctica with regular sprigs of mid-oceanic ridges. The origin of these regular structures is difficult to conform to chaotic movement of the lithosphere plates but it may be explained by the fluids-rotation conception proposed by the author. The conception supposes two main energy sources of the global tectonics: the degasification of the Earth (the fluids advection) and changes in the Earth rotation. Three basic stages of the tectonosphere formation are distinguished by the conception. Judging by the paleomagnetic data in ArcheanProterozoi several blocks of thick continental lithosphere were formed in the southern hemisphere. Geochemical studies show that the continental lithosphere was formed in from the mantle matter with large contents of fluids and it means that the intensive deep fluid flow has been at that time in the southern hemisphere. The formation of the thick lithosphere has led to asymmetry of a planet and to the relative displacement of the mass centers of the Earth’s spheres. That resulted in turning of the mantle around the core in Paleozoic with movement of the continental hemisphere to the north. Rotation of the mantle around the core created a new no equilibrium system. Therefore in Mesozoic era an expansion of the southern hemisphere began. Such expansion created the regular system of the mid-oceanic ridges forming a ring around Antarctica. Supposedly at the last stage the formation of the Antarctica continent on South Pole and destruction of a continental crust on the northern hemisphere (formation of the Arctic Ocean) took place to mount on the mass center balance.